Washington family collection
Correspondence, journals, financial papers, surveys, wills, deeds, genealogical notes, and other papers by or concerning family members related by blood or marriage to George Washington. Topics include the disposition of family property of George Washington and Martha Washington and the involvement of other family members in public affairs. Individuals represented include Burgess Ball, Bushrod Washington, Elizabeth Foote Washington, George Corbin Washington, Lund Washington, and Martha Washington.
Microfilm edition of an Elizabeth Foote Washington journal (1779 November-1796 December) is available
Microfilm produced from original in the Manuscript Division.
Chiefly photocopies and transcripts.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ball, Burgess, -- 1749-1800.; Washington, Bushrod, -- 1762-1829.; Washington, Elizabeth Foote, -- -1812.; Washington, George, -- 1732-1799 -- Estate; Washington, George, -- 1732-1799 -- Family; Washington, George Corbin, -- 1789-1854.; Washington, Lund, -- 1737-1796.; Washington, Martha, -- 1731-1802.; Washington, Martha, -- 1731-1802 -- Estate; Washington family